Islamic movements of Europe : public religion and Islamophobia in the modern world - Peter, Frank; Ortega, Rafael (Ortega Rodrigo) (Library of European studies, 2014)
Islam in Europe' and 'Islamophobia' are subjects of vital global importance which currently preoccupy policy-makers and academics alike. Examining various European Muslim groups and institutions that have branched off from Islamic movements - including the Muslim Brotherhood, Hizb ut-Tahrir and Jama'at-i Islami - this book outlines the configuration of social, political and religious processes that have given rise to new kinds of European Muslim organisations. It considers the relationship of these organisations to their 'parent' movements, their connections with transnational Islamic networks.